Terminology of kinship relations in the Russian language discourse of the 21st century - Yudina, Natalia (Przegląd Wschodnioeuropejski, 2018)
The paper reveals the peculiarities of the functioning of kinship relations terminology in Russian language discourse of the 21st century. The review of subject-oriented scientific literature and discourse use of relationship terms in fiction and mass media of the 20th – 21st century makes it possible to distinguish several tendencies in the functioning of relationship nominations in the Modern Russian language. They are characterized by interdisciplinary and synergetic features and demonstrate the unity of genealogical, mental, social, cultural and linguistic processes and principles typical for a modern Russian society.